Effect of separation techniques and regimes of cryopreservation on the structural and functional properties of cord blood nucleated cells - Зубов, П. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
In this paper the effectiveness of cryopreservation technology of cord blood using different cryoprotectants mechanism of action was assessed. The dependence of cord blood nucleated cells, including hematopoietic stem cells, safety viability and structural membrane integrity on the methods of their isolation and cryopreservation regimes was demonstrated. It has been shown that the application of non-penetrating cryoprotectant PEO-1500 (final concentration of 10%) or penetrating DMSO (final concentration of 5%) provide the preservation of cell structure and functional parameters after thawing.